2021
DOI: 10.1002/jbt.22870
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarein induces apoptosis and inhibits proliferation, migration, and invasion in ovarian cancer via inhibition of EZH2/FOXO1 signaling

Abstract: Scutellarein, a flavone found in the perennial herb Scutellaria baicalensis, has antitumorigenic activity in multiple human cancers. However, whether scutellarein can attenuate ovarian cancer (OC) is unclear. This study investigated the effects of scutellarein in OC. In vitro cell viability was assessed using MTT assay whereas proliferation was assessed using 5-ethynyl-2′-deoxyuridine and colony formation assays. Cell apoptosis was detected by an Annexin V-fluorescein isothiocyanate/ propidium iodide assay. Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Another study showed that it reduces tubular epithelial cell death and inflammation in ischemic kidney injury by degrading the COX-2 protein 61 . In colon and ovarian cancers, it inhibits metastasis and proliferation and induces apoptosis 62,63 . Beta-sitosterol and quercetin were found to enhance brain development and quercetin alleviates oxidative damage 64,65 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that it reduces tubular epithelial cell death and inflammation in ischemic kidney injury by degrading the COX-2 protein 61 . In colon and ovarian cancers, it inhibits metastasis and proliferation and induces apoptosis 62,63 . Beta-sitosterol and quercetin were found to enhance brain development and quercetin alleviates oxidative damage 64,65 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, farrerol induced cancer cell death through ERK activation in SKOV3 cells [ 23 ]. Scutellarein induced apoptosis and inhibited the proliferation, migration, and invasion of OC cells by blocking EZH2/FOXO1 signaling [ 24 ]. Liu et al reported that alkannin inhibited the viability, adhesion, invasion, and migration of human gastric cancer cell line MGC-803 through the toll-like receptor 2/nuclear factor-kappa B pathway [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was found that scutellarin promoted apoptosis and autophagy by activating the HIPPO–YAP signaling pathway, supporting the potential therapeutic application of scutellarin-based drugs to provide patients with breast cancer the best possible outcomes [ 151 , 152 ]. The potential benefits of scutellarin and scutellarein need more clinical investigation for cancer treatment and as a newer therapeutic option [ 153 , 154 , 155 , 156 , 157 ].…”
Section: Regulation Of Autophagy By Scutellaria Fl...mentioning
confidence: 99%